PEMERIKSAAN KADAR PESTISIDA DALAM DARAH PETANI BAWANG MERAH DI NAGARI ALAHAN PANJANG - Marisa, Marisa; Arrasyid, Akbar Septian (IAIN Batusangkar, 2017)
Purpose of this study to determine whether or not farmers exposed to pesticides the and the inhalation pesticide factors in blood on farmers of onion in Alahan Panjang. The population in this study was the farmers of onion in Alahan Panjang. The sample were 5 farmers. The research instrument by Cholinesterase test in the district LABKESDA Solok. Cholinesterase test result can be determined by mean of photometer 5010. Examination result in onion farmers Alahan Panjang village revealed that one of the farmers contained below normal Cholinesterase in blood. The inhalation pesticide factors on onion farmer can be caused by years of service or length of work, health status, lack of knowledge of farmers in the use the pesticide such as spraying exceeds the set time, do not wear personal protective equipment in the spraying and personal hygiene farmers. It is recommended that farmers Cholinesterase below normal not use pesticides before to cholinesterase returned to normal, and following the extension and use pesticide safely.